2003
DOI: 10.1046/j.1365-3032.2003.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Pheromones in relation to aggregation and reproduction in desert locusts

Abstract: Abstract. Desert locusts, Schistocerca gregaria (Forska˚l) (Orthoptera: Acrididae), exhibit a population density-dependent phase polymorphism which includes the gradual change of many morphological, physiological and behavioural characteristics. Many volatiles associated with desert locusts have been identified recently and it is assumed that they are involved in pheromonal control of behaviour and development of locusts. Ovipositing females deposit with their egg pods several volatiles that appear to be attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 51 publications
1
31
0
2
Order By: Relevance
“…In one case, a male passed paired locusts as if he had not noticed the presence of the female, the situation being similar to what has been reported in the laboratory (Seidelmann and Ferenz, 2002;Ferenz and Seidelmann, 2003).…”
Section: Ovipositing Behavior and Adult Body Colorationsupporting
confidence: 75%
“…In one case, a male passed paired locusts as if he had not noticed the presence of the female, the situation being similar to what has been reported in the laboratory (Seidelmann and Ferenz, 2002;Ferenz and Seidelmann, 2003).…”
Section: Ovipositing Behavior and Adult Body Colorationsupporting
confidence: 75%
“…The transition between the two phases is reversible before they reach the fourth or fifth instar (10). The gregarious traits and behavior are also regulated by pheromones (11,12), neuropeptides (13,14), and pigmentotrophin (15)(16)(17)(18). Even artificial physical stimulation on the hind legs of the desert locust can trigger phase transformation (11).…”
mentioning
confidence: 99%
“…These observations have been confirmed by similar studies (Simpson et al, 2001;Lester et al, 2005). Pheromones play a role in the control of behavior in locusts (Loher, 1990;Byers, 1991;Pener, 180 S. TANAKA 1991; Pener and Yerushalmi, 1998) and their chemical structures and significance were intensively studied in the last decade (Torto et al, 1994(Torto et al, , 1996Ferenz and Seidelmann, 2003;Hassanali et al, 2005). Recently, it was demonstrated that prolonged pre-copulatory mounting increases the length of copulation, which in turn increases the P 2 , the proportion of offspring sired by the second male to mate, in L. migratoria showing multiple mating .…”
Section: Phase Polyphenismmentioning
confidence: 61%